Poeci greccy w służbie Rzymu - Szastyńska-Siemion, Alicja (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2012)
The article discusses the Greek epigrammatists who were active in Rome during the principates of Augustus and Tiberius.
Keywords: poezja grecka; epigram; Antypater z Tessaloniki; Krinagoras; Parmenion poeta